1963
DOI: 10.1111/j.1151-2916.1963.tb19774.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐Strain Behavior of Titanium Dioxide (Rutile) Single Crystals

Abstract: A technique is described for testing rutile single crystals in compression at elevated temperatures.The stress-strain behavior of crystals of four different orientations was examined up to temperatures in excess of 1000°C, and a dependence of both the flow stress and the rate of work hardening on crystal orientation was observed. The results are discussed briefly in terms of the various slip systems found to operate in the differently oriented crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1964
1964
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 9 publications
2
30
0
Order By: Relevance
“…Discontinuities mark the onset of crack initiation and fracture (indicated by black arrows in Figure 3A). [57][58][59] The uniform and reproducible deformation behavior of the particles can also be seen from the EPL index data ( Figure 3B). The onset of particle cracking and fracture (in % arithmetic average) shows an inversed trend: it decreases from an initial value of 38.5%AE3.6% (as-prepared) to 14.6%AE0.8% for anatase and finally to 10.0%AE1.3% for the rutile particles.…”
Section: General Deformation Behaviormentioning
confidence: 59%
See 1 more Smart Citation
“…Discontinuities mark the onset of crack initiation and fracture (indicated by black arrows in Figure 3A). [57][58][59] The uniform and reproducible deformation behavior of the particles can also be seen from the EPL index data ( Figure 3B). The onset of particle cracking and fracture (in % arithmetic average) shows an inversed trend: it decreases from an initial value of 38.5%AE3.6% (as-prepared) to 14.6%AE0.8% for anatase and finally to 10.0%AE1.3% for the rutile particles.…”
Section: General Deformation Behaviormentioning
confidence: 59%
“…Compared to macroscopic titania samples, these values are exceptionally high: for the compression of single-crystalline rutile fracture strains of <3% were observed even at elevated temperatures. [57][58][59] The uniform and reproducible deformation behavior of the particles can also be seen from the EPL index data ( Figure 3B). For the different batches, the progression of the EPL index as function of the maximum strain shows the same trend and almost identical values.…”
Section: General Deformation Behaviormentioning
confidence: 84%
“…al. [ 16 ] studied the stress-strain relationships for rutile single crystals as a function of crystal orientation and compression axis and found that irrespective of the orientation, the favorable slip system remained {-101} < 101 > and {110} < 001 > , with the former being more favorable than the latter at lower stresses. [ 17 ] They also extensively studied TiO 2 fi lms by transmission electron microscopy (TEM) to characterize different defects.…”
Section: Tem Characterizationmentioning
confidence: 99%
“…8,9) The mobility of the dislocations, especially, is a crucial issue for controlling the misfit relaxation process through the gliding and climbing of misfit-related dislocations in heteroepitaxial growth. The most energetically preferential slip system in the rutile structure is 101 [101], although the Burgers vectors of [001] and 100 are shorter than that of 101 .…”
Section: Introductionmentioning
confidence: 99%